End-of-Life Caregivers and Profound Learning: A Grounded Theory Study - Davin J. Carr-Chellman; Michael Kroth; Donna Daniels; Corinne Brion; Lori Manzanares (Adult Education Research Conference, 2022)
This study developed a deeper understanding of profound learning as experienced by volunteer end-of-life caregivers. This paper shares preliminary results of the study, including the following findings: Kinds of Knowledges; Tools; Engages the Human Condition; Relational.
Keywords: profound learning; hospice; end-of-life caregiving